Preliminary study on the possible utilisation of bumblebee data in the assessment of seminatural habitats in the Ipoly valley - Sárospataki, Miklós (JOURNAL OF LANDSCAPE ECOLOGY, 2010)
Assessing the conservation value of a habitat, the insects, and other invertebrates are often overlooked. However, in these cases it should be very important to take into consideration the bees (Hymenoptera: Apoidea), because they are the most important pollinators, accordingly keystone species in the ecosystems. Bumblebees (Bombus sp.) can be good indicators of the naturalness of a habitat. This study tries to estimate the possibility of use of existing bumblebee data in evaluating conservation values of different habitats in the Ipoly valley. Unfortunately the existing data are not enough for exact estimations. We have specific data from only three places (Drégelypalánk, Ipolyhídvég, Ipolykér). In the case of establishing a monitoring system in the Ipoly valley, it is very important to take into consideration the bumblebees. If so, the selection of the sampling sites and the optimization of sampling effort are very important. The adequately collected bumblebee data should be capable as indicators of the conservation value of the given habitats.